Liver transplantation in a patient with hepatitis B, C and D coinfection associated with hepatocellular carcinoma: a management strategy for a rare condition. Case report - Dantas, Lucas Carvalho (2015)
CONTEXT: Orthotopic liver transplantation (OLT) is the treatment of choice for end-stage liver disease. Cirrhosis due to hepatitis C infection is the leading indication for liver transplantation worldwide. How-ever, patients who are given transplants because of viral liver diseases often present clinical coinfections, including hepatitis B together with hepatitis D. Currently, different strategies exist for patient management before and after liver transplantation, and these are based on different protocols developed by the special-ized transplantation centers. CASE REPORT: We present a rare case of a 58-year-old man with chronic hepatitis B, C and D coinfection. The patient developed cirrhosis and hepatocellular carcinoma. His treatment comprised antiviral therapy for the three viruses and OLT. The patient’s outcome was satisfactory. CONCLUSION: OLT, in association with antiviral therapy using entecavir, which was administered before and after transplantation, was effective for sustained clearance of the hepatitis B and D viruses. A recur-rence of hepatitis C infection after transplantation responded successfully to standard treatment compris-ing peginterferon alfa-2A and ribavirin.